SANGIRAN ANCIENT SITE AS A BATIK MOTIF IDEA AT “LIANASARI” CRAFTSMAN IN KLIWONAN VILLAGE, SRAGEN REGENCY - Syafi’, Muhammad; Gunadi (Universitas Negeri Semarang, 2025)
Sangiran Batik is a cultural heritage from ancestors originating from Sragen Regency, Central Java. The Sangiran Batik motif is inspired by various prehistoric discoveries at the ancient Sangiran site which has been recognized by UNESCO as a world cultural heritage. However, the general public's knowledge about Sangiran Batik is still minimal and not many craftsmen make it because the Sangiran Batik motif is classified as an old motif. However, there are also craftsmen who are aggressively developing batik motifs inspired by the Sangiran ancient site, namely the